Extracellular biofabrication of gold nanoparticles by using Lantana camara berry extract. Issue 1 (2nd January 2017) - Kumar, Brajesh; Smita, Kumari; Cumbal, Luis; Debut, Alexis
ABSTRACT: In the present study, the authors highlight the fabrication of gold nanoparticles (AuNPs) by using ripened berry extract of Lantana camara, which acted as a reductant and stabilizer both. The as-prepared AuNPs were further characterized by visual, UV-vis-NIR, and TEM with SAED, DLS, and XRD techniques. The formation of AuNPs is evidenced by the appearance of the pink color of the reaction mixture and a peak at λmax = 540, 1075 nm in the UV–vis spectra. TEM image analysis revealed that the AuNPs were mostly triangle and 150–300 nm in size. XRD and SAED analysis shows that the AuNPs are of a face-centered cubic structure and crystalline form. In addition, the experimental approach is simple, cost-effective, eco-friendly and reproducible at room temperature.